THE PROBLEM OF COOPERATIVE MANAGEMENT DEVELOPMENT (A CASE STUDY AT AL-FATIMAH ISLAMIC BOARDING SCHOOL IN BOJONEGORO) - Febryanti, Annisa Eka; Febryanti, Amelia; Fadhilah, Nandita Adhys Nur; Prastiyono, Hendri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Combining Islamic boarding school education with cooperative economic practices is one of the efforts to establish sustainable partnerships. Economic endeavours within the educational system often face ups and downs due to divided focus. Al-Fatimah is one of the most prominent Islamic boarding schools in Bojonegoro, East Java, and has developed cooperative businesses. This cooperative, named Al-Fatimah, operates as an independent business unit and engages in various fields, including MSMEs, laundry, food stalls, and a cafeteria, serving thousands of students. However, the cooperative's management is still not optimal. This research aims to uncover the factors hindering the development and strengthening of Al-Fatimah's cooperative management using a qualitative approach and a case study method. The research results indicate two factors influencing the development of Al-Fatimah's cooperative management: internal and external. Communication is an internal element, and capitalization is an external factor; both are crucial in sustaining the cooperative business at Al-Fatimah Islamic boarding school. Therefore, an improvement in communication and access to capital from partnerships, both internal and external to the boarding school, is needed to ensure the continuity of Al-Fatimah's cooperative.